Characterization of the ATP-Dependent Lon-Like Protease in Methanobrevibacter smithii. (28th April 2016) - Pei, Jihua; Yan, Jianfang; Jiang, Yi
Abstract : The Lon protease is highly evolutionarily conserved. However, little is known about Lon in the context of gut microbial communities. A gene encoding a Lon-like protease (Lon-like-Ms) was identified and characterized from Methanobrevibacter smithii, the predominant archaeon in the human gut ecosystem. Phylogenetic and sequence analyses showed that Lon-like-Ms and its homologs are newly identified members of the Lon family. A recombinant form of the enzyme was purified by affinity chromatography, and its catalytic properties were examined. Recombinant Lon-like-Ms exhibited ATPase activity and cleavage activity toward fluorogenic peptides and casein. The peptidase activity of Lon-like-Ms relied strictly on Mg 2+ (or other divalent cations) and ATP. These results highlight a new type of Lon-like protease that differs from its bacterial counterpart.